2020
DOI: 10.6018/analesps.411301
|View full text |Cite
|
Sign up to set email alerts
|

La especificidad conductual de la violencia filio-parental

Abstract: La violencia filio-parental (VFP) es un tipo de violencia intrafamiliar que ha cobrado visibilidad social y científica en los últimos años.  El objetivo de este estudio es analizar distintas formas de VFP y su relación con dos grupos de variables. Por un lado, el género, la edad, la estructura familiar, el curso, el rendimiento académico, el consumo de drogas, la frecuencia de dicho consumo y el diagnóstico de psicopatología. Por otro lado, la exposición a la violencia, el calor parental, el autoconcepto, el s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 66 publications
(86 reference statements)
0
20
0
1
Order By: Relevance
“…In relation to the type, violence, physical, or psychological, most of the studies on community and student samples found no significant gender differences in APV , whereas other studies reported girls exercised more psychological violence (Calvete et al, 2013;Rosado et al, 2017). In clinical and judicial samples, physical violence was mainly exercised by boys (Armstrong et al, 2018;Cortina and Martín, 2020), owing to the seriousness of the APV offense, this entailed a higher probability of custodial sentences, whereas girls were mainly involved in psychological violence. Nevertheless, other studies have found that girls in custody can also resort to severe forms of APV involving physical violence (Condry and Miles, 2014;Simmons et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In relation to the type, violence, physical, or psychological, most of the studies on community and student samples found no significant gender differences in APV , whereas other studies reported girls exercised more psychological violence (Calvete et al, 2013;Rosado et al, 2017). In clinical and judicial samples, physical violence was mainly exercised by boys (Armstrong et al, 2018;Cortina and Martín, 2020), owing to the seriousness of the APV offense, this entailed a higher probability of custodial sentences, whereas girls were mainly involved in psychological violence. Nevertheless, other studies have found that girls in custody can also resort to severe forms of APV involving physical violence (Condry and Miles, 2014;Simmons et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Owing to the social and legal involvements involved, the international scientific community is gradually shifting its focus toward this phenomenon but the number of specific APV studies still remains scarce (Gámez-Guadix and Calvete, 2012;Lyons et al, 2015). A recent systematic review (Simmons et al, 2018) has highlighted that the variations in the samples employed in previous studies and the plurality of definitions and measurements accounted for the discrepancies reported in the scientific literature (Gallego et al, 2019;Cortina and Martín, 2020;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, girls show higher levels of FC than boys and are more sensitive to family conflicts (Romero-Abrio et al, 2019). Second, the differential socialization of boys and girls in the family and its relationship with CPV must be taken into account (Cortina and Martin, 2020). For example, conflicts related to personal autonomy and independence are common during adolescence, especially in the case of girls who suffer more than boys from family restrictions that limit their freedom of conduct (Alonso-Stuyck and Aliaga, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In other terms, the hypothesis could be that girls are more involved in family conflicts than boys due to the sex-based differences in socialization; girls are also more sensitive to family conflicts and show higher levels of FC than boys. Consequently, girls not only suffer more discomfort and frustration but also generate more arguments and engage in more violence (mainly verbal) toward parents than boys (López-Martínez et al, 2019;Cortina and Martin, 2020).…”
Section: Discussionmentioning
confidence: 99%